Maqasid Syariah Management in Realizing Sustainable Development Goals: Perspective of the Halal Tourism Industry - Nurcahyo, Satria Avianda; Jannah, Roikhatul; Anis, Muhammad (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2024)
This research aims to explore in depth the application of Maqasid Syariah management in the Hajj and Umrah industry in Central Java and its contribution to achieving Sustainable Development Goals (SDGs). The Hajj and Umrah industry faces challenges in aligning Maqasid Syariah principles with management practices that support sustainability. This issue arises from the need to meet the spiritual and religious requirements of pilgrims while also making meaningful contributions to the Sustainable Development Goals (SDGs). The method used in this research is a qualitative method with a field interview approach, where data is collected through in-depth interviews with various Hajj and Umrah industry players, including travel agents, service providers and relevant regulators. Theoretically, this research contributes to the literature on integrating Maqasid Syariah into halal industry management, particularly in the Hajj and Umrah sector. The findings expand the concept of Syariah-based management by providing empirical evidence on how Maqasid Syariah principles—such as fulfilling basic needs, environmental protection, and community empowerment—can be applied to support sustainable development goals. Practically, the findings offer guidance to stakeholders in the Hajj and Umrah industry, including travel agencies, service providers, and regulators, in designing Maqasid Syariah-oriented management strategies. These findings may aid in developing community economic empowerment programs, environmental conservation initiatives, and inclusive services for pilgrims. This research concludes that Maqasid Syariah management has great potential for increasing the sustainability and competitiveness of the halal tourism industry in Central Java. It is hoped that the results of this research can provide insight for stakeholders in designing more effective policies and strategies to support a sustainable halal tourism industry.